Effect of water addition on the exergy balances of an LPG fuelled spark ignition engine. (2nd May 2005) - Ozcan, Hakan; Sait Soylemez, M.
In this paper, we investigate the effect of water addition on the exergy balance of a conventional engine. The present work is an analytical study depending on experimental measurements. A four-cylinder, LPG fuelled SI engine is used in this work, and water injection through intake manifold is used for water addition. The cylinder pressure versus crank angle, and water, air and fuel flow rates are measured during tests. The water injection is accomplished over water to fuel mass ratios of 0.5 to examine the corresponding second-law properties. The results of the exergy analysis of engine operation with water injection are compared with the results of similar analysis for no water injection cases. It is found that water injection increases the combustion irreversibility significantly.